PERAN WORLD HEALTH ORGANIZATION (WHO) DALAM MENANGGULANGI EPIDEMIK PENYAKIT DIFTERI DI INDONESIA PERIODE 2014-2017 - Muhammad Akbar, - (2019)
This study discusses about the outbreak of diphtheria in Indonesia, to see the roles and strategies of the Government of the Republic of Indonesia and the World Health Organization in overcoming the epidemic of diphtheria in 2014-2017. The conditions of outbreaks in Indonesia proves that the dynamics of diphtheria are getting worse every year. In the process of overcoming the existing diphtheria epidemic, the Government of Indonesia and the World Health Organization engage a coordinate with one-and-another to prepare a strategy that'll fix the domestic epidemic. In addition to the domestic, World Health Organization as a global health institution also forms a strategies to combat the epidemics within the region. This study raised the research question in the form of " How is the implementation of the Indonesian Government disaster diplomacy to WHO in an effort for tackling the epidemic of diphtheria in Indonesia 2014-2017 period ? ". To answer this question, researcher use related theories, which is concept of health security, the role theory of Intergovernment Organization, disaster diplomacy, and international cooperation. In the research methods, the author uses descriptive qualitative methods of research. The results of the study indicate that disaster diplomacy carries out by the Indonesian Government succeeded in attracting interest from WHO so that a joint strategy was formed to fight the diphtheria epidemic. Existing strategies and programs are good enough, but it needs to be improved in order to gain more widespread and equitable results